Analysis of Students Scientific Literacy Skills on Ecosystem Materials at Boalemo District Junior High School - Podungge, Rimlawaty; Nusantari, Elya; Katili, Abubakar Sidik; Dama, Lilan; Baderan, Dewi K; Mamu, Hartono D (Universitas Labuhanbatu, 2022)
This study aims to determine the level of scientific literacy skills of stutends on ecosystem learning material in Boalemo Regency Junior High School. The research applied a survey research type with a quantitative descriptive approach. The population in this study are 2 classes of 8th grade of SMP N 2 Dulupi with 42 students, A class of 8th grade SMP 8 Satap Dulupi with 26 students, and 5 classes of 8th grade of SMP N 1 Tilamuta with 120 students. The total samples amounted o 188 students. The sampling technique used random sampling. The research sample consisted of 60 students, consisting of 20 grade 8 students at SMPN 2 Dulupi, 20 grade 8 students at SMP 8 satap Dulupi, and 20 grade 8 students SMPN 1 Tilamuta. The instrument used is a question of students scientific literacy, which consists of 17 questions. The research data were analyzed using quantitative descriptive analysis. The results showed that the level of scientific literacy skills of students in Boalemo Regency Junior High School s was 54.4, which was in th â€œlowâ€ category. The scientific literacy level of students on multiple choice questions has an average score of 57.85 at SMP N 1 Tilamuta, 53.57 at SMP N 2 Dulupi, and 51.78 at SMP 8 Satap Dulupi. On the question of attitude assessment, the average score was 56.67 at SMP N 1 Tilamuta, 62.08 at SMP N 2 Dulupi, and 60.83 at SMP 8 Satap Dulupi.